Twinned power: formations of cloud-edge control. Issue 7 (19th May 2022) - Munn, Luke
ABSTRACT: From smart vehicles to smart city sensors, the millions of new devices connected over the next few years will generate huge amounts of highly personal data that needs to be processed in real time. Transmitting this data to the cloud, with its centralized data centers and high latency, is both economically and technically unviable. As a result, the industry is moving towards processing data closer to the source, a major shift from the cloud to the so-called edge. This new architecture is understood as a necessary augmentation to the cloud. Indeed, in many ways, the edge is the polar opposite of the cloud: ad hoc networks, composed of resource-poor devices, that function at the hyperlocal level of the home, office, or neighborhood. However, this article argues that such technical supplementation is also about control, filling a critical void in contemporary formations of power. Coupled together, this cloud-edge formation is both centralized and decentralized, resource intense yet geographically dispersed. Drawing on Foucauldian theory, such power augments heavy, situated force with a more flexible, economic architecture – conforming to a trajectory of 'intensification' while also complicating it. While each mode of power has certain strengths and weaknesses, combining their operations forms a twinned power with new capacities for subjectivation and governance.